If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y = 6 + -3x Solving 6y = 6 + -3x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '6'. y = 1 + -0.5x Simplifying y = 1 + -0.5x
| x=3-3y | | 7x(5+8)= | | 9=m/7 | | (2x+5)(x-1)=0 | | m^2-3m+4=0 | | 6=(63/7)-3 | | 6=(m/7)-3 | | 4m-16=32 | | 2(x-7)=15+4x | | 2x-7=15+4x | | 17-3a=5a+-16a | | x^3+3x^2=125 | | 2a^2+14a+24=0 | | 9.8*0.5*4= | | 10x-13=6x+1 | | 2x+9rtx-5=0 | | x^2+20x+7=0 | | 3(x+2)=x+(x+2)+(3x-1) | | X+X=(30*3*2) | | -6-3(2k+4)=-8 | | 4(2x-3)=-5 | | 3x(2x-3)=0 | | 6x^2+4x-54=0 | | 4x+6x=10x | | p+p+p+p= | | 19=3x | | X(4X+5)-3=0 | | X(4X+5)-3=5 | | 4(-4t^2+27-45)=0 | | 5x-3=-1 | | 9x^2+60x+100=0 | | 6(3-a)+7(3a+2)-4(a+5)= |